Virtual animation of the kinematics of the human for industrial, educational and research purposes
A source of high-quality data of both morphological and kinematics models of human joints will be created. The data will be collected by novel techniques developed by the proposers. These techniques will allow data to be obtained that is of potential interest in related fields across industry, medical education and research. At present, little accurate or reliable data concerning joint modelling is available, which often leads to simplification. Once created, the data will be available via the Internet to allow users to gain new knowledge on functional anatomy. Raw data will be available for downloading to allow industrial users to improve their own products and competitiveness. The interface will employ state-of-the-art multimedia techniques and 3D simulations in a virtual reality environment to demonstrate joint behaviour. Electronic tutorials will be supplied to help give medical staff and students to a better understanding of functional anatomy.